Design and Development of an ESP32 Based Barrier Gate Control System at PT. Bahana Security Sistem - Taufik Muchtar; Muslimin; Muhammad Syahdan Ali; Nur Aulia Arman (JEAT : Journal of Electrical Automation Technology, 2025)
PT. Bahana Security Sistem is a company engaged in the provision and management of parking systems. Currently, the company relies on proprietary parking control systems provided by third-party suppliers, which cannot be modified or tailored to meet specific operational requirements. This study presents the design and development of a barrier gate control system based on the ESP32 microcontroller for PT. Bahana Security Sistem. The system is designed to control the barrier gate using two access control methods: Push Button and Radio Frequency Identification (RFID). An experimental approach was adopted, consisting of system design, hardware implementation, testing, and performance evaluation. The results indicate that the proposed system performs effectively, achieving a 100% success rate in operating the barrier gate using both access methods. Based on the test results, the developed system meets the operational needs of PT. Bahana Security Sistem.